Translation Strategy of English Phrasal Verb in Novel “The Devil All The Time” By Pollock - Reyhan Milzan Fernanda; Yeni Noryatin; Inta Masni Sinaga; Ade Surista (Sekolah Tinggi Bahasa Asing JIA, 2022)
This study aims to analyze the translation strategy of the Phrasal Verb in the novel The Devil All the Time. The theory used in this study is the kinds of phrasal verb from Wyatt and theory of Baker for the translation strategy. This study used qualitative descriptive method. The result of the study showed that: there are five phrasal verb found in this novel, namely, 15 intransitive phrasal verb(48,38%), 9 transitive phrasal verb where the object can come in one of two positions (29,03%), 2 transitive phrasal verbs where the object must come between the verb and the particle (6,45%), 3 transitive phrasal verbs where the object must come after the verb and the particle (9,67%), 2 transitive phrasal verbs with two object, one object is between verb and particle and the other one after the particle (6,45%);there are 4 types of translation strategies used by the translators of this novel, namely, data 9 translation by a more general word (29,03%), 14 translations by a more neutral/less expressive word (45,17%), 6 translations by paraphrase using a related word (19,35%), 2 translations by paraphrase using unrelated words (6,45%).